Total Quality Management (TQM) and Basic Education: Its Application to Islamic Education in Muhammadiyah Elementary Schools - Busahdiar; Ummah Karimah; Sudirman Tamin (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – The purpose of this study is to observe and explain the improvement in the quality problems of elementary schools in the Muhammadiyah organization to encourage a quality management system. The research was conducted at Muhammadiyah 24 Rawa Mangun Elementary School, Jakarta. Design/methods/approach – This study used qualitative methodologies through data collection techniques like interviews with key informants in the school environment, field observations, analytical documentation studies, and examination of previous research findings. The collected data was analyzed using data reduction, presentation, and verification. Findings – Research findings showed that SD Muhammadiyah 24 Rawamangun implements a quality management system. The pattern of TQM implementation starts from the parent's quality, where then each part/function sets quality objectives that refer to and are aligned with the parent's quality goals. They include the sequence of processes, activities, facilities and documents used, teaching and learning process activities, and other supporting activities carried out by SD Muhammadiyah 24 Rawamangun, evaluation and supervision conducted in process stages under evaluation and supervision procedures. Not to mention maximum achievements in terms of TQM since it involves various educational instruments - namely qualified educators and education personnel, students, curriculum, facilities, and processes as well. Research implications/limitations – This study highlights the importance of quality management assurance in improving the education quality in primary schools. Future research could investigate the impact of specific quality management assurance practices on the academic outcomes of SD Muhammadiyah 24 Rawamangun. Originality/value – The study provides unique insights into the impact of quality management assurance on specific academic outcomes, which can inform future research in education.